Türkiye’de Popülizm ve Demokrasi: Cumhuriyet Halk Partisi Örneği - Boyraz, Cemil (İstanbul Bilgi Üniversitesi Yayınları, 2020)
-Abstract- This study will examine the main opposition party in Turkey, the Republican People’s Party (CHP) and discusses the constitutive role of populism in the party’s discourse. Therefore, this study will highlight and
Populism and Democracy in Turkey: The Case of the RepublicanPeople’s Party
Keywords: Populism; the Republican People’s Party; left-populism; social democracy; Turkey; Popülizm; Cumhuriyet Halk Partisi; sosyal demokrasi; sol-popülizm